2019
DOI: 10.1123/ijspp.2018-0851
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation Patterns Correlate With Race Walking Economy in Elite Race Walkers: A Waveform Analysis

Abstract: Purpose: To analyze the association between muscle activation patterns on oxygen cost of transport in elite race walkers over the entire gait waveform. Methods: A total of 21 Olympic race walkers performed overground walking trials at 14 km·h−1 where muscle activity of the gluteus maximus, adductor magnus, rectus femoris, biceps femoris, medial gastrocnemius, and tibialis anterior were recorded. Race walking economy was determined by performing an incremental treadmill test ending at 14 km·h−1. Results: This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These rules distinguish race-walking from walking and running, making race-walking possesses a unique locomotor strategy different from other sports (Zhang et al, 2019). Physiological studies had shown that race-walking has higher restricted joint biomechanics and muscle energy costs than running (Cronin et al, 2016;Gomez-Ezeiza et al, 2019). Therefore, investigating the motor mechanisms of race-walking might be crucial for practitioners of this discipline.…”
Section: Introductionmentioning
confidence: 99%
“…These rules distinguish race-walking from walking and running, making race-walking possesses a unique locomotor strategy different from other sports (Zhang et al, 2019). Physiological studies had shown that race-walking has higher restricted joint biomechanics and muscle energy costs than running (Cronin et al, 2016;Gomez-Ezeiza et al, 2019). Therefore, investigating the motor mechanisms of race-walking might be crucial for practitioners of this discipline.…”
Section: Introductionmentioning
confidence: 99%